The Great Electoral Battle. the Photographic Cliché Evolution About the Vote in the Beginners Twenty Century in Chile [la Gran Batalla Electoral. la Evolución del Cliché Fotográfico del Voto a Principios del Siglo Xx en Chile] - Roman-Alvarez, E; Jara-Reyes, R (Universidad Complutense de Madrid, 2019)
The present article describes the relationship between electoral practice and its representation in the context of an incipient mass culture. To do this, we have selected a list of photo-reports published in Chilean illustrated magazines of the time (1903-1920), in which we analyze the continuities and discontinuities in the forms of representation of the modern ritual of the vow. In this way, we observe how the use of certain clichés is part of a strategy of journalistic representation of the elections that collaborates with the work of legitimizing the vote as the main republican ceremonial. This article reports on two simultaneous processes: on the one hand, it is about the representation of the expansion of the right to vote and, on the other hand, about how the printed images assume as their own the challenge of democratizing society from the images. © 2019 Universidad Complutense de Madrid. All rights reserved.